WEB-BASED TECHNICAL SUPERVISION AND PLANNING REPORTS INFORMATION SYSTEM IN CV. TATA SAKA CONSULTANT - Krisna Ajie Prasetyo; Arief Kelik Nugroho (Jurnal Teknik Informatika (Jutif), 2022)
Information System of Technical Supervision and Planning Reports is a web-based system that is used to manage the process of supervision and technical planning activities in the CV. Tata Saka Consultant. The process in this system is focused on the process of collecting and archiving reports on activities carried out by employees. CV. Tata Saka Consultant which is a civil works consulting company domiciled in the city of Purbalingga and has routine activities in providing planning and supervision services to the Public Works Department. Because the process of collecting and archiving activity reports that are still manual and has not been computerized so that errors often occur in the placement of archiving reports of activities carried out by employees, the main purpose of this system is to help the process of gathering and archiving activity reports become more structured. The method used in the development of the Information System for Supervision and Technical Planning Reports is the Prototyping development method which requires a lot of discussion and evaluation between developers and users so that the system developed can be fully in accordance with what is expected by the user. Development on this system uses the Hypertext Preprocessor (PHP) programming language, Hypertext Markup Language (HTML), Cascading Style Sheets (CSS), JavaScript and uses the MySQL database with the Black-box testing method. After all testing is carried out, this system is stated to increase efficiency and effectiveness in the implementation of planning and technical supervision activities at CV. Tata Saka Consultant based on the assessment obtained from all users.